2023
DOI: 10.3390/cells12162077
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Therapies against Myocardial Ischemia-Reperfusion Injury: From Basic Science to Clinical Perspectives

Lejla Medzikovic,
Tara Azem,
Wasila Sun
et al.

Abstract: Mortality from myocardial infarction (MI) has declined over recent decades, which could be attributed in large part to improved treatment methods. Early reperfusion is the cornerstone of current MI treatment. However, reoxygenation via restored blood flow induces further damage to the myocardium, leading to ischemia-reperfusion injury (IRI). While experimental studies overwhelmingly demonstrate that females experience greater functional recovery from MI and decreased severity in the underlying pathophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 190 publications
0
4
0
Order By: Relevance
“…It is noteworthy that sex differences play essential roles in determining the pharmacokinetics and pharmacodynamics of drugs. Previous studies have demonstrated that many cardiovascular drugs display sex-biased responses [ 52 ], and emerging evidence from clinical trials indicates that the efficacy of various new drugs targeting cardiac I/R injury is associated with potential sex differences [ 53 ]. This study showed that EG extract protects against cardiac I/R injury in male rats, but its pharmacological action on female animals is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that sex differences play essential roles in determining the pharmacokinetics and pharmacodynamics of drugs. Previous studies have demonstrated that many cardiovascular drugs display sex-biased responses [ 52 ], and emerging evidence from clinical trials indicates that the efficacy of various new drugs targeting cardiac I/R injury is associated with potential sex differences [ 53 ]. This study showed that EG extract protects against cardiac I/R injury in male rats, but its pharmacological action on female animals is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…MI due to atherosclerotic or thrombotic occlusion of coronary arteries leads to ischemia in the myocardium. While rapid reperfusion is the cornerstone of current MI treatment, restoring blood flow leads to further damage to the myocardium by causing ischemia-reperfusion injury (IRI) [4]. An IRI is characterized by oxidative stress, cell death, inflammation, and fibrosis.…”
Section: Myocardial Infarction and Cardiac Ischemia-reperfusion Injurymentioning
confidence: 99%
“…MI due to atherosclerotic or thrombotic occlusion of coronary arteries leads to ischemia in the myocardium and cardiomyocyte death. Rapid reperfusion is the cornerstone of current MI treatment, but restoring blood flow leads to further damage to the myocardium by causing ischemia-reperfusion injury (IRI) [4]. Cardiac fibrosis is excessive extracellular matrix production and contributes to numerous cardiac disorders by impairing myocardial compliance, contractility, and electrical conductance [5].…”
Section: Introductionmentioning
confidence: 99%
“…Time-dependent effects of nitrate in OVX rats have been reported previously; for example, glucose-lowering and anti-osteoporotic effects of nitrate have been observed only after 6 months of intervention ( Yousefzadeh et al, 2022b ; Yousefzadeh et al, 2022c ). In addition, compared to males, following ischemia, females have reduced myocardial IR injury ( Besík et al, 2007 ) and infarct size ( Bae and Zhang, 2005 ), as well as higher eNOS and neural NOS (nNOS) expression ( Sun et al, 2006 ) and lower apoptosis ( Chen et al, 2013 ; Medzikovic et al, 2023 ) in heart tissue. Therefore, the current study was designed to investigate whether the long-term (9 months) nitrate administration provides resistance against myocardial IR injury in OVX rats.…”
Section: Introductionmentioning
confidence: 99%